The impact of human resources and work attitude on the performance of employees at PTPN V Tanjung Medan Oil Palm Plantations / Isnu Widodo and Bakhtiar - -, Isnu Widodo; -, Bakhtiar (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
The issue in this study is the low degree of human asset advancement at PTPN V oil palm estates Tanjung Medan Kec. Pujud Rokan Hilir and the absence of familiarity with the significance of focusing on demeanor. The relationship has positive ramifications comparable to the work conduct of an individual at PTPN V Tanjung Medan oil palm ranch, Pujud Rokan Hilir locale. This sort of exploration utilizes quantitative examination. The population in this study was 153 workers, with an example of 153 representatives. The examining strategy in this study utilized immersed testing with the assistance of SPSS Rendition 22 for Windows information handling programs. The information examination utilized numerous direct relapses, and the accompanying outcomes were: The consequences of the halfway test (t test) on the human asset improvement variable were t-count 3.109 > t-table 2.0129, and that really implies that there is a positive and huge effect on the presentation of PTPN V oil palm manor employees. while for the motivation variable, the incomplete experimental outcome (t test) is tcount 1.936 > ttable 2.0129 Sig. 0.00 > 0.05, which actually intends that there is an impact of work disposition on the presentation of PTPN V oil palm manor representatives. In view of the consequences of the synchronous test, the Fcount esteem is 15.108, the Ftable is 2.81 (15.108 > 0.05), and the huge level is under 0.05, to be specific (0.00 <0.05), and that implies there is a critical positive impact between the impact of human asset improvement and work perspectives on representative execution. In light of the trial of the coefficient of assurance, the value of the changed R square is 0.463 (46.3%). This implies that the capacity of the autonomous variable in this study influences the dependent variable by 46.3%, while the remaining 53.7% can be made sense of by factors other than the free factor.